THE HISTORY OF GEOLOGICAL AND PALEONTOLOGICAL STUDY OF BOLSHOYE BOGDO MOUNTAIN - I. A. Starodubtseva; I. V. Novikov (Известия высших учебных заведений: Геология и разведка, 2018)
The history of the geological and paleontological study of Bolshoye Bogdo mountain, as well as the evolution of the views on their geological structure, has been considered.The first descriptions of the rocks composing the Bolshoye Bogdo mountain, published in the 18th century by academicians S.G. Gmelin and P.S. Pallas, have been given. A particular attention has been paid to the results obtained during the expedition conducted under the guidance of the English geologist R.I. Murchison in 1841. A great contribution to the knowledge of the geological structure and paleontological characteristics of Bolshoye Bogdo mountain was made by A.B. Auerbach, who discovered here the remains of Triassic temnospondyl amphibians and fish for the first time for the territory of European Russia. A new stage in the study of the paleontology of the Bolshoye Bogdo mountain, which began in 1912, has been characterized. A well-known paleontologist and writer LA. Efremov worked there in the 1926th and 1928th years and conducted scientific research and searches for vertebrate remains. Later, the study of the geological structure of the Bolshoye Bogdo mountain was carried out by the staff of the Saratov State University, Borissiak Paleontological Institute and other scientific institutions of Russia.